Prediction of angular kyphosis after cervical laminoplasty using radiologic measurements. (March 2021) - Jeon, Hyeongseok; Kim, Hyung-Cheol; Kim, Tae Woo; An, Seong Bae; Shin, Dong Ah; Yi, Seong; Kim, Keung Nyun; Yoon, Do Heum; Borkar, Sachin A.; Son, Dong Wuk; Ha, Yoon
Abstract: Angular kyphosis is an important complication after cervical laminoplasty. Previous reports have suggested that T1 slope (T1s) and extension function (EF) have key roles in kyphosis, and no different radiologic measuments which affects postoperative kyphosis were seen between ossification of the posterior longitudinal ligament (OPLL) or cervical spondylotic myelopathy (CSM). We tried to find preoperative radiologic measurements predicting angular kyphosis after laminoplasty according to disease entities. We retrospectively analyzed 133 patients with OPLL or CSM who underwent expansive laminoplasty. Preoperative neutral and extension C2-7 cobb angle (CA), T1s, C2-7 sagittal vertical axis, and C2-7 slope angle (SA) were measured. EF of C2-7 CA and C2-7 SA was defined as extension CA/SA minus neutral CA/SA. Significant angular kyphosis was defined as LCL less than −10° after surgery. Mean loss of lordosis was −3.23, and 16.5% of patients showed significant kyphosis. Preoperative EF-CA, EF-SA, and T1s were found to be predictive for angular kyphosis by Pearson correlation analysis. The receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) of radiologic measurements could not reach 0.7. In patients with OPLL, the AUC of preoperative neutral CA was 0.716. However, in patients with CSM ROC curve analysis revealed that EF-CA and EF-SA could predict the significant angular kyphotic changes. Examining OPLL and CSM separately, preoperative radiologic measurements were found to influence postoperative cervical kyphosis, respectively. However, preoperative C2-7 neutral CA in OPLL patients and both EF-CA and EF-SA in CSM patients could predict significant angular kyphosis after cervical laminoplasty.